ANTIHYPERTENSIVE EFFICACY AND INFLUENCE ON SEXUAL FUNCTION OF VALSARTAN AND VALSARTAN AND HYDROCHLOROTHIAZIDE COMBINATION IN SMOKERS VERSUS NON-SMOKERS WITH ARTERIAL HYPERTENSION - V. I. Podzolkov; A. V. Vigdorchik (Столичная издательская компания, 2015)
Aim. To study antihypertensive efficacy and safety of valsartan-based therapy as well as influence of treatment on several aspects of sexual function. Material and methods. Hypertensive patients (n=650) in 53 medical institutions of Russia were enrolled to the prospective multicenter observation study, 37.5% of smokers and 62.5% non-smokers. The evaluation of therapy efficacy was based on analysis of systolic (SBP) and diastolic (DBP) blood pressure (BP) changes. Safety and compliance of treatment was also analyzed. The evaluation of sexual function was performed with 5 universal questions selected form the International Index of Erectile Function. These ques- tions could be asked in both men and women. The valsartan dose was 80-320 mg OD. A combination of the valsartan with hydrochlorothiazide (12.5-25 mg/d), amlodipine (5-10 mg/d) or any other antihypertensive was allowed. Results. Significant similar decrease of SBP and DBP was observed in smoking and non-smoking patients (37.4/17.8 and 36.7/16.5 mm Hg respectively, р<0.01 vs baseline). Differences in SBP and DBP changes were not significant between groups. Target BP level (<140/90 mmHg) was reached in 81.9% smokers and 76.0% non-smokers. After 20 weeks of treatment the number of patients without sexual activity and with 1-2 successful sexual attempts in the last 4 weeks significantly decreased from 44.7 to 32.8% and from 29.1% to 23.2%, respectively (р<0.05). Significant increase in the number of patients with 5-6 and 7-10 successful sexual attempts was observed (from 6.1 to 13.6% and from 3.2 to 5.9% respectively, р<0.05). The treatment resulted in significant increase in the number of patients, who evaluated their sexual life satisfaction as "very satisfied" (from 8.2 to 14.8%, <0.01). Conclusion. Comparable antihypertensive efficacy and safety were demonstrated for valsartan based therapy in smoking and non-smoking patients. During the course of treatment there was a significant improvement of sexual function and general satisfaction with sexual life in patients with arterial hypertension, which could have favorable long-term consequences in increased compliance to the antihypertensive therapy.